Effectiveness of in-Tray Early Waring System Training on Knowledge and Practice of Nurses - Nuraidah, Nuraidah; Widiantari, Aninda Dinar; Maemun, Siti; Hutabarat, Veronika; Khamid, Abdul; Wahyuning, Indah; Sumaryati, Sumaryati; Ambarwati, Desi; Murtiani, Farida (GLOBAL HEALTH SCIENCE GROUP, 2024)
Death marks the conclusion of the disease trajectory. Prevention of fatality in patients facing acute and chronic diseases requires the competence of reliable health workers, with nurses playing a crucial role in delivering proficient care. Aiming for early detection of patients' clinical deterioration, nurses use an early warning system. Objective: to determine the effectiveness of EWS training in-tray method on knowledge and practice of EWS. We conducted a quasi-experimental study using one group pretest-posttest without a control group. The sample of this study was 70 executive nurses with consecutive sampling techniques. The research was held at the Inpatient Installation of Sulianti Saroso Infectious Disease Hospital (SSIDH) in June 2023. Observation sheets were utilized to assess Early Warning System (EWS) practices, and we employed valid and reliable questionnaires to gather information on respondents' knowledge. We performed univariate analysis using frequency distribution and bivariate analysis using the Wilcoxon test. Most respondents were in the late adult category (52.9%), female (80.0%), graduate Diploma III in nursing education (54.3%), and the most working period of 5 years (78.6%). The knowledge of participants increased significantly from 7.00 (2.00-13.00) (pretest) to 11.50 (5.00-20.00) (posttest) (p-value = 0.000). There was an increase in nurses' EWS knowledge and practice (p-value <0.05). Efforts to improve nurse competence in caring for patients with critical conditions are necessary. This can be achieved through coaching and regular training with the priority target of implementing nurses in the intensive care room.